Could a cooperation network between Finnish universities advance adoption and success of Green Office environmental management system? - Malinen, Liisa-Maija (2013)
Finnish universities are increasingly adopting EMSs in order to improve their sustainability performance. Theoretical background includes studies on EMS implementation in universities and sustainability networks. Insufficient management commitment leading to lack of resources and time has been identified as a common hindering factor with regard to implementation of said systems. This study is an empirical research on the possibilities of an inter- university network in facilitating the implementation of the Green Office EMS. The study is providing answers to the following questions: whether a university Green Office cooperation network could assist the progress of the programme and in what way? What aspects of the programme implementation a cooperation network is and is not likely to provide benefits in? What issues do the Green Office coordinators see potentially impeding successful operation of a university cooperation network and finally would they be interested in joining such a network? The data was collected by thematic interviews of five Finnish university Green Office coordinators and analysed based on the subjects’ background information as well as the set themes i.e. network’s effect on exchange of ideas and good practices; bureaucratic aspects of Green Office; innovation generation; joint projects and curriculum; motivation; and marketing. The findings indicate that the main benefits for universities from network cooperation would be from exchange of ideas and good practices, motivation, and joint projects and curriculum. Also, the opportunities an active university network could provide innovation generation, were apparent. Bureaucratic aspects as well as marketing emerged as unlikely to benefit from university partnerships. Importance of management commitment in the success of an environmental management system implementation arose as an additional theme through both the statements of subjects and practical examples of the universities’ operations. The study also provides information on the shortcomings of the Green Office programme when applied to the educational sector. Main hindering factors with regard to effectiveness of an inter- university network were a lack of time and resources for the Green Office coordinators as well as the amount of existing networks and thus, a risk of overlapping. In managerial implications this study presents a design for a university network based on virtual networking technologies as well as useful feedback to WWF Finland.